Enhanced quantum entanglement in the non-Markovian dynamics of biomolecular excitons (2009)
We show that quantum coherence of biomolecular excitons is maintained over exceedingly long times due to the constructive role of their non-Markovian protein-solvent environment. Using a numerically exact approach, we demonstrate that a slow quantum bath helps to sustain quantum entanglement of two pairs of Forster coupled excitons, in contrast to a Markovian environment. We consider the crossover from a fast to a slow bath and from weak to strong dissipation and show that a slow bath can generate robust entanglement. This persists to surprisingly high temperatures, even higher than the excitonic gap and is absent for a Markovian bath.